THYROID CHANGES IN INFANTS OF MOTHERS WITH GRAVES’ DISEASE: A CASE SERIES - Nordin , Farah Nursyahirah Binti; Teik, Teoh Sze (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Maternal Graves' disease (GD) can affect neonatal thyroid function. Maternal factors such as timing of diagnosis, TSH-receptor Ab (TRAb) titre, anti-thyroid medications and prior radioiodine therapy will affect outcome. CASE We describe six infants born to mothers with GD (2 mothers diagnosed before pregnancy and 4 mothers during pregnancy) in Hospital Sultanah Bahiyah in 2023–2024. All mothers had elevated TRAb, from 3.34 IU/L to >40 IU/L, taken at 16–35 weeks of gestation. Five were treated with carbimazole (10–40 mg daily). Four started treatment during pregnancy and one prior to pregnancy. One mother had RAI before pregnancy and her infant had negative TRAb. Two (2/6) neonates had low birth weight and four (4/6) were premature. One neonate had fetal goiter and required elective LSCS via EXIT procedure by paediatric ORL. This neonate’s goitre resolved following L-thyroxine initiation and was extubated within 3 days. Four neonates had elevated TRAb ranging 11.2 IU/L to 39.5 IU/L. Within 1st week, five had hyperthyroidism, of whom, one was symptomatic for moderate tachycardia. Two required low dose carbimazole for 4–6 weeks. The highest fT4 was 61.24 pmol/L. One patient with no thyrotoxicosis initially developed central hypothyroidism by 1-month-old. Of those with initial transient hyperthyroidism, three (3/5) developed central hypothyroidism thereafter requiring L-thyroxine. Two of them (2/3) had transient central hypothyroidism that resolved between 2-month-old and 1-year-7-month-old. By the time of report, three (3/6) infants still require L-thyroxine of whom two (2/3) had central hypothyroidism with prior hyperthyroidism. All these infants have appropriate growth and development during follow-up. CONCLUSION It is crucial to ensure mothers with GD have early diagnosis and adequate monitoring during pregnancy to prevent neonatal complications. Infants of maternal GD should be monitored closely and at regular intervals, to detect alteration of thyroid function which is important for brain development.